2014
DOI: 10.1080/00325481.2014.994468
|View full text |Cite
|
Sign up to set email alerts
|

United States comparative costs and absenteeism of diabetic ophthalmic conditions

Abstract: DME and DR are associated with substantial direct medical cost and absenteeism in this real-world sample of medically insured employees. This research highlights the negative impact of DME and DR on annual costs and absenteeism and may assist employers in assessing the impact of these conditions on employees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…A study of US employees aged 18–64 years with DR found that the subgroup who had a DME diagnosis cost their employers 75% more than the subgroup who did not have a DME diagnosis (annual direct health care plus indirect work loss costs of $28,606 vs $16,363 in 2005 USD, P <0.0001) 23. High cost and resource use trends (with varying degrees of statistical significance) were also reported for DME in two parallel analyses of US commercial drivers and nondriver employees: drivers with DME and nondrivers with DME had higher costs (annual health care costs of $12,511 and $17,433 in 2012 USD, respectively) than their diabetic controls without DME ($8,785 and $10,926, respectively), missed more work days (27 and 14 days, respectively) than their diabetic controls without DME (15 and 9 days, respectively), and were more likely to use health benefits across a range of services (medical care, prescriptions, sick leave, disability, and workers’ compensation) than their respective control groups 16. In the current study, working-age diabetic patients with DME also utilized more health care resources in terms of both the proportions of patients utilizing services and the mean number of visit days by utilizers than the matched non-DME patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A study of US employees aged 18–64 years with DR found that the subgroup who had a DME diagnosis cost their employers 75% more than the subgroup who did not have a DME diagnosis (annual direct health care plus indirect work loss costs of $28,606 vs $16,363 in 2005 USD, P <0.0001) 23. High cost and resource use trends (with varying degrees of statistical significance) were also reported for DME in two parallel analyses of US commercial drivers and nondriver employees: drivers with DME and nondrivers with DME had higher costs (annual health care costs of $12,511 and $17,433 in 2012 USD, respectively) than their diabetic controls without DME ($8,785 and $10,926, respectively), missed more work days (27 and 14 days, respectively) than their diabetic controls without DME (15 and 9 days, respectively), and were more likely to use health benefits across a range of services (medical care, prescriptions, sick leave, disability, and workers’ compensation) than their respective control groups 16. In the current study, working-age diabetic patients with DME also utilized more health care resources in terms of both the proportions of patients utilizing services and the mean number of visit days by utilizers than the matched non-DME patients.…”
Section: Discussionmentioning
confidence: 95%
“…Although DME can affect adults of any age, its implications may be different among different age segments. Working-age adults with DME may suffer most due to loss of work productivity and employment stability,16 while elderly patients may have increased caregiver needs and social isolation due to DME 17. Underlying risks of associated diabetes-related comorbidities may also differ by age.…”
Section: Introductionmentioning
confidence: 99%
“…Psychosocial and socioeconomic factors we looked into did not reveal any meaningful correlation as well. Patients' profession and measured quality of life have been shown to affect patient adherence to treatment in previous studies nevertheless, [64][65][66][67] with vision loss due to DME producing a significant socioeconomic strain on communities. 68 Stress, discomfort, and fear from possible side effects have been shown to have an effect on compliance.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] DME treatment is associated with substantial direct medical costs for the patient, absenteeism for working patients and need for carer’s assistance for injection appointments. [ 8 , 9 ] Moreover, patients report anxiety and high expectations that lead to negative impact on long term anti-VEGF therapy and cause some delay in schedule a new appointment for intravitreal injection. Results from real-life studies are not comparable with the data known from randomized control trials, revealing that the actual number of anti-VEGF injections administered and the proportion of patients achieving significant BCVA gain are lower.…”
Section: Introductionmentioning
confidence: 99%